Review of the millipede genus Yasudatyla Shear & Tsurusaki, 1995 new to the fauna of Russia, with description of new species from the Kurile Islands (Diplopoda, Chordeumatida, Conotylidae) - Mikhaljova, Elena V. (Zootaxa, 2015)
The diplopod genus Yasudatyla Shear & Tsurusaki, 1995 is new to the fauna of Russia, due to the discovery of Y. kurilensis sp. nov. from Kurile Islands. The genus is currently represented by four species, i.e. Y. yasudai Shear & Tsurusaki, 1995, Y. hidakaensis Shear & Tsurusaki, 1995, Y. shariensis Shear & Tsurusaki, 1995, all from Japan, and Y. kurilensis sp. nov. from the Kurile Islands, Russia, described here. All known species of the genus are keyed, including the new species.